A minimally-intrusive fully 3D separated plate formulation in computational structural mechanics - Quaranta, Giacomo; Ziane, Mustapha; Haug, Eberhard; Duval, Jean-Louis; Chinesta, Francisco (Advanced modeling and simulation in engineering sciences, 2019)
Most of mechanical systems and complex structures exhibit plate and shell components. Therefore, 2D simulation, based on plate and shell theory, appears as an appealing choice in structural analysis as it allows reducing the computational complexity. Nevertheless, this 2D framework fails for capturing rich physics compromising the usual hypotheses considered when deriving standard plate and shell theories. To circumvent, or at least alleviate this issue, authors proposed in their former works an in-plane–out-of-plane separated representation able to capture rich 3D behaviors while keeping the computational complexity the one of 2D simulations. In the present paper we propose an efficient integration of fully 3D descriptions into existing plate software.